Karakteristik Kuat Geser Tanah Gambut Teluk Gelam - Siti Muslikah; Ahmad Hasan Afrizal; Hermawati Hermawati; Yosieguspa Yosieguspa; Sri Yulianti; M. Rafiq Wahiputra (Universitas Muhammadiyah Palembang, 2026)
Peat soil is formed from material origin comprising the rest of tehe dead plants and surrounded by state of the environment is always submerged in water. Peat soils have less favorable technical properties that have a high enough water content, low shear strength and behavior peat soils very in each location. This causes challenges for thecivil engineering for the devolopment of infrastructure. This testing is done in laboratory soil mechanics sriwijaya university to determine shear strength parameters peat soil Teluk Gelam located in the district Ogan Komering Ilir. Testing results on peat soil Teluk Gelam, Ogan Komering Ilir district can be classified as peat soil with a high water contentamounted to 721,556 %, with moderate or ash content (medium ash peat) between 5-15%, and contain fiber content< 20% included in the category of Amorphous peat. Cohesion value (C) obtained “7 kN/m2 as well as the angle of the sliding (?) : 1,01°. Shear strength value (?) on peat soil Teluk Gelam has a low shear strenght is 10,8925 kN/m2.